2014
DOI: 10.1128/aem.03880-13
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic Androgen Degradation by the Denitrifying Bacterium Sterolibacterium denitrificans via the 2,3-seco Pathway

Abstract: eThe biodegradation of steroids is a crucial biochemical process mediated exclusively by bacteria. So far, information concerning the anoxic catabolic pathways of androgens is largely unknown, which has prevented many environmental investigations. In this work, we show that Sterolibacterium denitrificans DSMZ 13999 can anaerobically mineralize testosterone and some C 19 androgens. By using a 13 C-metabolomics approach and monitoring the sequential appearance of the intermediates, we demonstrated that S. denitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“… Genes involved in ring AB degradation – The degradation of ring A in the oxygen‐independent 2,3‐ seco pathway involves the Mo‐enzyme AtcABC converting androst‐1‐en‐3,17‐dione to a 1,3‐di‐keton (Wang et al ., ; Yang et al ., ). Highly homologous genes are present in the acd 3 gene cluster (SDENv1_10172‐4; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Genes involved in ring AB degradation – The degradation of ring A in the oxygen‐independent 2,3‐ seco pathway involves the Mo‐enzyme AtcABC converting androst‐1‐en‐3,17‐dione to a 1,3‐di‐keton (Wang et al ., ; Yang et al ., ). Highly homologous genes are present in the acd 3 gene cluster (SDENv1_10172‐4; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…denitrificans (Yang et al ., ). The A ring is then hydrolytically cleaved to 1,17‐dioxo‐2,3‐ seco ‐androstan‐3‐oic acid (DSAO), the name‐giving key intermediate of this 2,3‐ seco ‐pathway (Wang et al ., ). The genes and enzymes involved in DSAO formation/degradation are unknown.…”
Section: Introductionmentioning
confidence: 97%
“…strain Aa7, that is able to grow with bile salts as sole carbon source under anoxic conditions with nitrate as electron acceptor. There are only a few studies on the bacterial degradation of steroid compounds under denitrifying conditions, which mainly focused on the metabolism of cholesterol and testosterone (Chiang et al ., ; Fahrbach et al ., ; Wang et al ., ; ; Yang et al ., ; Warnke et al ., ; ). To the best of our knowledge, this is the first study showing bacterial degradation of the steroid skeleton of bile salts under denitrifying conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Stl. denitrificans uses the 2,3-seco pathway (see Figure 1b for detailed information) to degrade androgens regardless of oxygen conditions (Wang et al, 2013a;Wang et al, 2014), and no genes encoding steroid catabolic oxygenases are found in the Stl. denitrificans genome (Dermer and Fuchs, 2012).…”
Section: Sdomentioning
confidence: 99%
“…denitrificans DSMZ 18526 (gammaproteobacterium) and Sterolibacterium (Stl.) denitrificans DSMZ 13999 (betaproteobacterium) as model microorganisms (Wang et al, 2013b(Wang et al, , 2014 (Figure 1b). However, information regarding the catabolic genes and enzymes involved in the anaerobic catabolic pathway is scant.…”
Section: Introductionmentioning
confidence: 99%